2023
DOI: 10.3390/nu15081987
|View full text |Cite
|
Sign up to set email alerts
|

Independent and Joined Association between Socioeconomic Indicators and Pediatric Obesity in Spain: The PASOS Study

Abstract: Childhood obesity is a public health problem worldwide. An important determinant of child and adolescent obesity is socioeconomic status (SES). However, the magnitude of the impact of different SES indicators on pediatric obesity on the Spanish population scale is unclear. The aim of this study was to assess the association between three SES indicators and obesity in a nationwide, representative sample of Spanish children and adolescents. A total of 2791 boys and girls aged 8 to 16 years old were included. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 56 publications
0
1
0
2
Order By: Relevance
“…In addition, the measurement invariance for three socio-economic variables relevant to the family environment, such as education, income, and marital status, was confirmed. It was shown that these three variables influence the way parents act with respect to the problem of childhood obesity [ 62 , 63 ], and this invariance allows for comparisons of scores on this scale between these groups of parents to be made in subsequent analyses. Also, to ensure gender invariance, it will be necessary to reach a larger group of fathers, which, in view of the low level of interest shown in this first field test, will require specific sampling (probably face-to-face sampling).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the measurement invariance for three socio-economic variables relevant to the family environment, such as education, income, and marital status, was confirmed. It was shown that these three variables influence the way parents act with respect to the problem of childhood obesity [ 62 , 63 ], and this invariance allows for comparisons of scores on this scale between these groups of parents to be made in subsequent analyses. Also, to ensure gender invariance, it will be necessary to reach a larger group of fathers, which, in view of the low level of interest shown in this first field test, will require specific sampling (probably face-to-face sampling).…”
Section: Discussionmentioning
confidence: 99%
“…Crianças e adolescentes cujos pais tinham nível superior escolar apresentaram uma probabilidade menor de 34% de desenvolverem obesidade grave, quando comparados aos que tinham pais com uma escolaridade menor. Logo, entender a associação entre a desigualdade socioeconômica e obesidade infantil é crucial, para combater o crescente aumento dessa doença (Homs et al, 2023).…”
Section: Yang Et Al (2022)unclassified
“…A OMS pontuou a urgência de reduzir as desigualdades socioeconômicas, como uma forma de prevenção para a obesidade infantil. Em alguns países, foram implementados impostos sobre bebidas açucaradas e o regimento da publicidade em alimentos e bebidas não saudáveis, para crianças com menos de 16 anos (Homs et al, 2023).…”
Section: Yang Et Al (2022)unclassified